Efficient, direct synthesis of dimethyl carbonate from CO2 using a solid, calcined zirconium phenylphosphonate phosphite catalyst - Unnikrishnan, Pulikkeel; Varhadi, Poonam; Srinivas, Darbha (RSC Advances, 2013)
Direct synthesis of dimethyl carbonate (DMC) from CO2 and methanol with 100 mol% selectivity using a solid, reusable, hydrophobic, calcined zirconium phenylphosphonate phosphite catalyst is reported for the first time. DMC yield as high as 26 mmol g(-1) catalyst correlated with the concentration of acid and base sites is obtained.